2022
DOI: 10.1136/bmjopen-2022-062332
|View full text |Cite
|
Sign up to set email alerts
|

Life after COVID-19: the road from intensive care back to living – a prospective cohort study

Abstract: ObjectivesThe aim of the study was to evaluate recovery of participation in post-COVID-19 patients during the first year after intensive care unit (ICU) discharge. The secondary aim was to identify the early determinants associated with recovery of participation.DesignProspective cohort study.SettingCOVID-19 post-ICU inpatient rehabilitation in the Netherlands, during the first epidemic wave between April and July 2020, with 1-year follow-up.ParticipantsCOVID-19 ICU survivors ≥18 years of age needing inpatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…In this study, the predominance of males was notable, and it was probably men who were most alerted to the possibility of participating in this study, which has also been commonly found in other similar studies [18]. Regarding the age group, there is an alignment with the standard values for this population.…”
Section: Discussionsupporting
confidence: 77%
“…In this study, the predominance of males was notable, and it was probably men who were most alerted to the possibility of participating in this study, which has also been commonly found in other similar studies [18]. Regarding the age group, there is an alignment with the standard values for this population.…”
Section: Discussionsupporting
confidence: 77%
“…There was also a diversity in the target of the interventions. There were interventions and services that intended to manage COVID-related (20,35,39) and fatigue symptoms (11,13,14,16,20,22,25,29,30,40), train speci c skills to alleviate functional de cits (13, 15, 16, 20, 22, 23, 27, 29, 31-34, 36, 41), facilitate activities of daily living (11, 12, 25, 27-29, 32, 33, 36, 40, 42) and work-related training (13, 17, 23, 29, 34-36, 40, 42), educate patients on self-management techniques (14, 16, 18-20, 24, 28, 31-33, 35, 40, 43), and adapt the physical and social environments (11,13,15,16,23,33,34). However, we must disclaim that occupational therapists were involved in some, and not in all, interventions and services for clients with PCC and RTW needs.…”
Section: The Occupational Therapy Process and Outcomes In Rtwmentioning
confidence: 99%
“…A total of 42 studies were assessed; 20 studies involving 1254 patients were included in the quantitative synthesis and 19 studies were used for the meta-analysis. The number of studies (i.e., number of patients) reporting an instance of return-to-work at 0-3 months, 4-6 months, and 7-12 months were three [15][16][17], eleven [18][19][20][21][22][23][24][25][26][27], and eight [17,25,[27][28][29][30][31][32], respectively. Studies in which outcome assessments were conducted over an extended time frame were excluded.…”
Section: Study Selectionmentioning
confidence: 99%
“…All the included studies were published from 2021 to 2023 (Table 1). Two studies [23,32] were conducted in the United States, 16 in Europe [15,17,18,[20][21][22][24][25][26][27][28][29][30][31]33,34], one in Brazil [16], and one in Australia [19].…”
Section: Study Characteristicsmentioning
confidence: 99%